2012
DOI: 10.1103/physrevstper.8.010111
|View full text |Cite
|
Sign up to set email alerts
|

Observations on student difficulties with mathematics in upper-division electricity and magnetism

Abstract: We discuss common difficulties in upper-division electricity and magnetism (E&M) in the areas of Gauss's law, vector calculus, and electric potential using both quantitative and qualitative evidence. We also show that many of these topical difficulties may be tied to student difficulties with mathematics. At the junior level, some students struggle to combine mathematical calculations and physics ideas, to account for the underlying spatial situation when doing a mathematical calculation, and to access appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
134
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 45 publications
11
134
0
3
Order By: Relevance
“…Many alumni mentioned particular techniques (e.g., Laplace's equation) in their comments about the course, indicated that the course ''expanded my mathematical toolkit,'' and one specifically claimed that, ''I became more mathematically sophisticated.'' Our observations indicate that students typically struggle to apply these abstract mathematical tools to physical systems (i.e., analyzing a problem to choose the appropriate tool or limits of integration), and to make physical meaning of their answer [6].…”
Section: Mathematical Sophisticationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many alumni mentioned particular techniques (e.g., Laplace's equation) in their comments about the course, indicated that the course ''expanded my mathematical toolkit,'' and one specifically claimed that, ''I became more mathematically sophisticated.'' Our observations indicate that students typically struggle to apply these abstract mathematical tools to physical systems (i.e., analyzing a problem to choose the appropriate tool or limits of integration), and to make physical meaning of their answer [6].…”
Section: Mathematical Sophisticationmentioning
confidence: 99%
“…While physics education researchers have examined the teaching of electricity and magnetism (E&M) at the introductory level in some detail [3,4], research on upper-division E&M is still fairly limited [4][5][6] and documentation of experimental course approaches are rare [7]. However, preliminary experimental evidence suggests that upperdivision students are not achieving the level of skill that is expected of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of papers on the transformation of upper-division courses that use novel methods or curriculum, but they have very limited measures of learning and, with one exception, no such comparative data indicating the superiority of one teaching method over another. For example, some PER work on upper-division courses has focused on the characterization of persistent difficulties with fundamental concepts [3] and mathematics [4] that hinder meaningful learning of advanced topics. This work motivated the creation and use of tutorials where the instructor has small groups of students work collaboratively on worksheets that guide them through proper reasoning to overcome misconceptions and gain physical insight or that simply provide supervised practice of key mathematical tools [3,5].…”
Section: A Existing Per Literature On the Effectiveness Of Upper-divmentioning
confidence: 99%
“…The study of student understanding of advanced topics is becoming increasingly prevalent in physics education research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Investigating upper-division undergraduate students provides a snapshot of the intellectual journey from novice introductory student to expert physicist that may reveal key components of this transition [19].…”
Section: Introductionmentioning
confidence: 99%